2013
DOI: 10.1210/en.2013-1291
|View full text |Cite
|
Sign up to set email alerts
|

Hexarelin Treatment in Male Ghrelin Knockout Mice after Myocardial Infarction

Abstract: Both ghrelin and the synthetic analog hexarelin are reported to possess cardioprotective actions that are mainly exerted through different receptors. However, their effects on acute myocardial infarction have not been compared in vivo. This study aimed to clarify whether hexarelin treatment can compensate for ghrelin deficiency in ghrelin-knockout mice and to compare the effects of hexarelin (400 nmol/kg/d, sc) and equimolar ghrelin treatment after myocardial infarction. Myocardial infarction was produced by l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 40 publications
0
24
0
Order By: Relevance
“…The results showed that hexarelin-treated mice had better cardiac function than ghrelin-treated mice, as indicated by the higher absolute values of percent of the ejection fraction (EF), peak rate of pressure rise (dP/dt max) and dP/dt min, fractional shortening (FS), preload-adjusted maximal power (PAMP), and maximal elastance (Emax). Hexarelin and ghrelin treatments also significantly reduced collagen volume fraction in the noninfarcted LV walls and plasma atrial natriuretic peptide levels than vehicle administration [175]. These stronger effects of hexarelin was also confirmed by another study in which hypophysectomized rats were treated in vivo for 7 days with either ghrelin (320 g/kg) or hexarelin (80 g/kg), and then their hearts were subjected in vitro to the ischemia and reperfusion procedure [172].…”
Section: Ghrelin and Hexarelin Promote Mitochondrial Activity And Biomentioning
confidence: 66%
See 1 more Smart Citation
“…The results showed that hexarelin-treated mice had better cardiac function than ghrelin-treated mice, as indicated by the higher absolute values of percent of the ejection fraction (EF), peak rate of pressure rise (dP/dt max) and dP/dt min, fractional shortening (FS), preload-adjusted maximal power (PAMP), and maximal elastance (Emax). Hexarelin and ghrelin treatments also significantly reduced collagen volume fraction in the noninfarcted LV walls and plasma atrial natriuretic peptide levels than vehicle administration [175]. These stronger effects of hexarelin was also confirmed by another study in which hypophysectomized rats were treated in vivo for 7 days with either ghrelin (320 g/kg) or hexarelin (80 g/kg), and then their hearts were subjected in vitro to the ischemia and reperfusion procedure [172].…”
Section: Ghrelin and Hexarelin Promote Mitochondrial Activity And Biomentioning
confidence: 66%
“…Ghrelin ( To compare the effect of ghrelin and hexarelin on cardiac function after infarction MI, ghrelin-knockout mice were used to show whether hexarelin could compensate for the ghrelin deficiency [175]. The results showed that hexarelin-treated mice had better cardiac function than ghrelin-treated mice, as indicated by the higher absolute values of percent of the ejection fraction (EF), peak rate of pressure rise (dP/dt max) and dP/dt min, fractional shortening (FS), preload-adjusted maximal power (PAMP), and maximal elastance (Emax).…”
Section: Ghrelin and Hexarelin Promote Mitochondrial Activity And Biomentioning
confidence: 99%
“…Previous studies have indicated that the cardiovascular action of hexarelin occurs through the activation of two cardiac receptors, GSHR1a receptors and CD36 receptors. 19) However, the changes in intracellular signaling pathways and gene expressions induced by receptor activation have not been fully clarified. In our study, we observed down-regulation of IL-1β expression and up-regulation of IL-1Ra expression in I/R myocardium after hexarelin treatment, which could be interrupted by the GHSR1a antagonist [D-Lys3]-GHRP-6.…”
Section: Discussionmentioning
confidence: 99%
“…18) These effects are considered to be mediated not only by GHSR1a but also by activation of cardiac CD36 receptors. 19) The existence of cardiac GHSR1a and CD36 receptors indicates hexarelin has direct cardiovascular effects independent of growth hormone (GH) release and neuroendocrine stimulation, which was also proved by several studies. 8) [D-Lys3]-growth hormone releasing peptide-6 ([D-Lys3]-GHRP-6), a GHSR1a antagonist, can block the effects of both ghrelin and hexarelin.…”
mentioning
confidence: 90%
“…As its synthetic analogue, Hex 82 showed similar effects to ghrelin through the GH secretary and cardiac protection. Finnaly, a cardiovascular study demonstrated that Hex had more potent beneficial effect than ghrelin; while Hex displayed greater improvement of heart function on ghrelin-null mice after myocardial infarction compared to equimolar administration of ghrelin [363]. Previous investigation also showed that ghrelin (10nmol/L) or Hex (1nmol/L) exerted the same positive inotropic effect on cardiomyocytes after ischemia/reperfusion injury [259].…”
Section: Chapter Six -General Conclusion and Future Directionmentioning
confidence: 98%